PENGARUH KEMAMPUAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA AUDITOR INSPEKTORAT PROVINSI RIAU - Amalia Khairunnisa; Kirmizi Ritonga; Al Azhar Lukman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine: 1) the effect on the performance of the auditor's intellectual capabilities, 2) the effect of emotional intelligence on the performance of the auditor and 3) the influence of spiritual intelligence on the performance of auditors.The sample used in this study were all auditors Inspectorate Riau Province. Collecting data through a questionnaire survey method. Of the 41 questionnaires distributed, the number of questionnaires returned was 41. The data using multiple regression analysis (multiple regression) with the help of a computer program SPSS version 17.0.The results showed that: 1) The ability Intellectual positive significant effect on the Performance Auditor, 2) Emotional Intelligence positive significant effect on the Performance Auditor and 3) Spiritual Intelligence positive significant effect on the Performance Auditor .It can be concluded that the coefficient of determination 0604 or 60.4%. This figure is 60.4% explained that the auditor's performance is influenced by intellectual ability, emotional intelligence and spiritual intelligence. While the remaining 39.6% auditor's performance is explained by other variables that are not included in this study.Keywords: Ability Intellectual, Emotional Intelligence, Spiritual Intelligence, Performance Auditor.